Signature and function of plasma exosome-derived circular RNAs in patients with hypertensive intracerebral hemorrhage - Chen, Kejie; Cheng, Xiaoyuan; Yuan, Shanshan; Sun, Yang; Hao, Junli; Tan, Quandan; Lin, Yapeng; Li, Shuping; Yang, Jie (Molecular genetics and genomics : MGG, 2024)
Intracerebral hemorrhage (ICH) is one of the major causes of death and disability, and hypertensive ICH (HICH) is the most common type of ICH. Currently, the outcomes of HICH patients remain poor after treatment, and early prognosis prediction of HICH is important. However, there are limited effective clinical treatments and biomarkers for HICH patients. Although circRNA has been widely studied in diseases, the role of plasma exosomal circRNAs in HICH remains unknown. The present study was conducted to investigate the characteristics and function of plasma exosomal circRNAs in six HICH patients using circRNA microarray and bioinformatics analysis. The results showed that there were 499 differentially expressed exosomal circRNAs between the HICH patients and control subjects. According to GO annotation and KEGG pathway analyses, the targets regulated by differentially expressed exosomal circRNAs were tightly related to the development of HICH via nerve/neuronal growth, neuroinflammation and endothelial homeostasis. And the differentially expressed exosomal circRNAs could mainly bind to four RNA-binding proteins (EIF4A3, FMRP, AGO2 and HUR). Moreover, of differentially expressed exosomal circRNAs, hsa_circ_00054843, hsa_circ_0010493 and hsa_circ_00090516 were significantly associated with bleeding volume and Glasgow Coma Scale score of the subjects. Our findings firstly revealed that the plasma exosomal circRNAs are significantly involved in the progression of HICH, and could be potent biomarkers for HICH. This provides the basis for further research to pinpoint the best biomarkers and illustrate the mechanism of exosomal circRNAs in HICH.